More than Skin Deep: Sea Surface Temperature as a Means of Inferring Atlantic Water Variability on the Southeast Greenland Continental Shelf Near Helheim Glacier. Issue 4 (21st April 2021) - Snow, T.; Straneo, F.; Holte, J.; Grigsby, S.; Abdalati, W.; Scambos, T.
Abstract: Enhanced outlet glacier discharge accounts for almost half of the Greenland Ice Sheet's mass loss since 1990. Warming subsurface Atlantic Water (AW) has been implicated in much of that loss, particularly along Greenland's southeastern coast. However, oceanographic observations are sparse prior to the last decade, making it difficult to diagnose changes in AW properties reaching the glaciers. Here, we investigate the use of sea surface temperature (SST) measurements to quantify ocean temperature variability on the continental shelf near Sermilik Fjord and Helheim Glacier. We find that after removing the short‐term, atmospheric‐driven variability in non‐winter months, regional SSTs provide a reliable upper ocean (surface mixed layer) temperature record. In the trough region near Sermilik Fjord, the adjusted SSTs correlate well with moored ocean measurements of the water entering the fjord at depth and driving glacier melting. Using this relationship, we reconstruct the AW variability on the shelf dating back to 2000, 8 years before the first mooring deployments. Across the 19‐year record, the AW temperatures in the trough do not always track properties in the source waters of the Irminger Current, which flows along the continental break. Instead, the properties of the waters found at the fjord mouth depend on variations in the source AW and, also, in the Polar Water that flows into the region from the Arctic Ocean. Satellite‐derived SSTs, when combined with local oceanography considerations, have the potential to improve understanding around previously unanswered glacier‐ocean questions in areas surrounding Greenland. Plain Language Summary: Greenland ice contributes one‐quarter of global sea level rise each year and almost half of that loss comes from glaciers at its periphery. Warming ocean waters may cause much of that loss. Records produced from ocean instruments are the main method for studying the oceans around Greenland, but few observations exist prior to the last decade. In this work, we investigate the use of sea surface temperatures (SSTs) acquired by satellites to assess ocean temperature changes through time. We explore their use near the southeastern Greenland coast, where warm water circulates from the North Atlantic Ocean onto the continental shelf and eventually reaches Helheim Glacier, Greenland's fifth largest glacier. Through a comparison with ocean instruments, we find that SSTs serve as a good indicator of upper ocean temperatures in this region once proper corrections are applied. With these records, we find that the dilution of warm waters as they circulate from the North Atlantic changes over time and governs the temperature of the water that eventually reaches Helheim, which was previously unknown. Our work shows that SSTs can provide new insight into the ocean changes that may have affected glacier retreat before ocean instruments were deployed. Key Points: Sea surface temperatures (SSTs) measure upper ocean temperatures after variability tied to the atmosphere is removed Once adjusted for air temperature, SSTs near the fjord reflect deep Atlantic Water (AW) temperatures entering Sermilik Fjord Dilution of AW as it intrudes onto the continental shelf modulates nearshore temperatures